Effect of Oven and Microwave Heating on the Total Antioxidant Capacity of Dietary Onions Grown in Turkey - Ozyurt, Dilek; Goc, Binnur; Demirata, Birsen; Apak, Resat (Informa UK Limited, 2013)
The active components of largely consumed dietary onions (Allium species) in Turkey were extracted with water and ethanol, separately heated in a drying oven (at 50°C, for 1–4 h) and in a microwave oven (at 90 W, for 1–4 min), and their total antioxidant capacity was determined with different electron transfer-based assays. Five different onion species/aerial parts, namely yellow, red, white, fresh green leaf, and fresh green root, were measured for total antioxidant capacity with different methods, the hierarchic order in aqueous extracts being: CERAC: yellow-skinned > red-skinned > spring-root > spring-leaf > white-skinned onion; CUPRAC: spring-leaf > red-skinned > spring-root > yellow-skinned > white-skinned onion; Folin-Ciocalteau method: spring-leaf > spring-root > red-skinned > yellow-skinned > white-skinned onion. Using all three methods, white onion, showed the lowest total antioxidant capacity, while with respect to two methods (i.e., CUPRAC and Folin-Ciocalteau), spring onion-leaf showed the hig...